Is performance at young age a good predictor of later success? - Li, P.; de Bosscher, V. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Most countries attempt to develop systematic structures to identify gifted talented athletes and to promote their development in certain sports. However, forecasting years in advance for the next generation of sport experts is challenging. The aim of this study is to facilitate talent identification and development program by identify a critical age at which athletes should start to perform in international competitions, and to what extent it is reliable to use junior success as a criterion to predict senior success. Methods: The preliminary research consists of a European analysis of four sports: judo, tennis, gymnastics and athletics. This case study uses a top down approach to collect data in answering the question: how did senior elite athletes performed during youth tournaments? The sport specific principles were chosen in consultation with representatives of the Flemish Sport Federations. We focused first on correlations between performances on youth tournaments and professional level. Second, we shed light on how elite athletes performed in the selected youth tournaments (top down approach). Results: The conducted correlations were all significant but ranged from very weak-to-weak correlations. As a result, junior athletes with better performances at the selected youth tournaments appear to have a slightly greater chance to be successful at the elite athlete level. Secondly, we conclude that there is an uncertainty about the relationship of performances on youth tournaments and success of elite athletes. The result also reveals that a third of all world-class athletes for athletics, judo as well as gymnastics did not perform or participate in the selected youth tournaments. Discussion: These results indicate the general good to put into perspective the relative importance of performances at young ages. Moreover, a mixture of physical and mental skills into appropriate action is common for all sports and each sport is marked by a singularity of required sport-specific elements for successful performance (Baker & Horton, 2004). The ages at which transitions occur as well as the duration of the stages are sport-specific (Wylleman, Alfermann, & Lavallee, 2004). Therefore, it should be indicated that the youth performance sports index is only one out of many parameters evaluating the development of young athletes.